Human Genetics for the Social Sciences. - Carey, Dr. Gregory (Advanced Psychology Text Series., 2002)
There is a growing awareness of the important role that human genetics play in individual differences in human behavior. However, many behavioral scientists have little background in biology, much less training in genetics. This book is for students in the behavioral sciences who need to understand genetics, but who have little or no training in biology. The text provides the basic biology which is essential for an understanding of genetics and then provides a solid overview of the principles of genetics. Rather than provide a comprehensive analysis of the current literature on genetics, the.